(untitled) (Research, Society and Development, 2022)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disease whose main characteristic is the increase in the blood glucose index (hyperglycemia), caused by a deficiency in the production of insulin by the body. Objective: To verify in national and international publications the importance of nursing work in the face of possible microvascular and macrovascular complications in patients with Type 2 Diabetes Mellitus (T2DM). Methodology: Narrative literature review study. For the conduction, the following research question will be formulated: What is the importance of nursing work in cardiovascular complications in patients with Type 2 Diabetes Mellitus? The search was performed in the following databases: BDENF-BIREME, Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (Scielo), WorldWideScience and Dialnet. Results: ADMT2 is a pathology that has been increasingly worrying the world health agencies due to the continuous increase in prevalence and incidence in recent decades that directly contributes to the development of cardiovascular complications. Complications of T2DM include diabetic retinopathy, diabetic neuropathy, diabetic kidney disease and sexual dysfunction, which are microvascular. occurrences of acute myocardial infarction, heart failure, and coronary artery disease are observed as the main macrovascular complications, which are directly related to systemic arterial hypertension, dyslipidemia and obesity. Final considerations: Nurses’ priority activity is the adoption of intensive management, with strict control of cardiovascular risk factors in diabetic patients.